The 2nd International Cell Death Research Congress 2018
DOI: 10.3390/proceedings2251529
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Relation between Follicular Atresia and Granulosa Cells in Terms of Cell Death Mechanisms in Premature Ovarian Failure Model

Abstract: Premature Ovarian Failure; is characterized by the dysfunction or early depletion of ovarian reserves due to follicular loss in the ovary in women under age of 40. POF is the important cause of infertility and its etiology is still not clearly understood. Investigation of cell death mechanisms (CDM) that play a role in the follicular atresia (FA) triggered by excessive loss of granulosa cells (GCs) that provide metabolic support for oocyte and follicle development in the ovary will help to understand POF etiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Follicular atresia and premature ovarian failure are related to GCs apoptosis. 40,41 Although significant progress has been made in ovarian physiology, some specific molecular regu- and CCND1 were detected by RT-qPCR. F, The protein levels were detected by western blot analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Follicular atresia and premature ovarian failure are related to GCs apoptosis. 40,41 Although significant progress has been made in ovarian physiology, some specific molecular regu- and CCND1 were detected by RT-qPCR. F, The protein levels were detected by western blot analysis.…”
Section: Discussionmentioning
confidence: 99%
“…GCs are important cellular components of the ovary. Follicular atresia and premature ovarian failure are related to GCs apoptosis 40,41 . Although significant progress has been made in ovarian physiology, some specific molecular regulatory mechanisms for follicular development are still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have confirmed that the selection and atresia of follicles are determined by the apoptosis of GCs [ 47 , 48 ]. In addition, one of the mainstream views on the mechanism underlying the onset of POF caused by chemotherapeutic drugs is that POF is the result of follicular atresia caused by the excessive senescence, apoptosis, and loss of GCs [ 10 , 11 ]. Therefore, it is very important to improve the ovarian functions and restore the fertility of patients by inhibiting the apoptosis of GCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism underlying the POF caused by chemotherapeutic drugs is still unclear [ 9 ]. There are two mainstream views: (1) POF is the result of follicular atresia caused by excessive senescence, apoptosis, and loss of granulosa cells (GCs) [ 10 , 11 ]; and (2) POF is the result of excessive activation of dormant primordial follicles [ 12 , 13 ]. In order to study the mechanism of chemotherapeutic drugs damaging ovarian function, this study chooses phosphoramide mustard (PM) to conduct in vitro cell experiments.…”
Section: Introductionmentioning
confidence: 99%